2011
DOI: 10.1139/h11-098
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the effects of methylphenidate on energy intake in young adults: a preliminary study

Abstract: The present study examined gender differences in response to methylphenidate (MPH) on energy intake and macronutrient preference. Twelve adults (6 men, 6 women) were given placebo or short-acting MPH (0.5 mg/kg) in a randomized, double blind, placebo-controlled crossover fashion. One hour after drug administration, appetite sensations and the relative reinforcing value of energy-dense snack food were measured, followed immediately by energy intake and macronutrient preference during a buffet lunch. Relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…In the present study, chronic MP treatment was associated with sex-dependent differences in fluid and food intake as previous studies similarly reported (Goldfield et al, 2007, Goldfield et al, 2011, Davis et al, 2012). Although previous studies collectively agree that chronic MP treatment modulates fluid and food intake, their findings have been inconsistent.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, chronic MP treatment was associated with sex-dependent differences in fluid and food intake as previous studies similarly reported (Goldfield et al, 2007, Goldfield et al, 2011, Davis et al, 2012). Although previous studies collectively agree that chronic MP treatment modulates fluid and food intake, their findings have been inconsistent.…”
Section: Discussionsupporting
confidence: 89%
“…Psychostimulants suppress appetite [27, 28] and may lead to body weight reduction following chronic exposure [29]. Indeed, during the treatment phase, we observed decreased fluid intake in both LD and HD treated rats compared to the water treated rats, and decreased food intake and body weight only in the HD treated rats.…”
Section: Discussionmentioning
confidence: 64%
“…For instance, treatment with this drug lowers body weight faster in male than in female rats and reduces total fluid intake in male only . In addition, in normal‐weight humans, methylphenidate decreases energy intake more in men than in women, whereas in patients with obesity, it significantly reduces appetite, cravings, and snack‐food intake only in women . A stronger anorectic effect in women than men has been observed in the response to methylphenidate also in binge eating disorders .…”
Section: Phentermine/topiramate Combinationmentioning
confidence: 99%